14th AIAA/CEAS Aeroacoustics Conference (29th AIAA Aeroacoustics Conference) 2008
DOI: 10.2514/6.2008-2883
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin-Helmholtz Instabilities Occurring at a Nacelle Exhaust

Abstract: The difference of flow velocity between the free stream and the jet stream at a nacelle exhaust generates a shear layer where some hydrodynamic instabilities, called Kelvin-Helmholtz instabilities, can occur. Some instabilities occur in the shear layer in the computations with Actran/DGM a time domain code which solves the LEE equations (see, 1 , 2 and 3 ) but it is often difficult to conclude whether they are physical or not. This document recalls the theory on the Kelvin-Helmholtz instabilities and gives gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Additionally this type of mean flow, containing a strong velocity shear layer, can generate instabilities in LEE simulations. Methods exist to obtain stable solutions (see Zhang and Chen, 44 Manera et al, 45 and Ewert and Shr€ oder, 46 for example), but their use is beyond the scope of this work. Therefore, inviscid mean flow solutions are used here to avoid these potential issues.…”
Section: Modeling Aoa and Cambermentioning
confidence: 97%
“…Additionally this type of mean flow, containing a strong velocity shear layer, can generate instabilities in LEE simulations. Methods exist to obtain stable solutions (see Zhang and Chen, 44 Manera et al, 45 and Ewert and Shr€ oder, 46 for example), but their use is beyond the scope of this work. Therefore, inviscid mean flow solutions are used here to avoid these potential issues.…”
Section: Modeling Aoa and Cambermentioning
confidence: 97%
“…it follows that the forcing frequency is of the same order of magnitude of the momentum thickness of the mean shear flow. Under these conditions it can be shown that the vortical mode is excited and hydrodynamic flow oscillations, induced by the associated Kelvin–Helmholtz instability, occur. Figures (a) and (b) show the instantaneous LEE and APE solutions at t = 16, respectively.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In the physical flow, such modes are controlled by viscous and non-linear effects, absent in an LEE model. In some instances the mixing layers grow sufficiently rapidly for the growth of the KH instabilities to be controlled by the spreading effect [18]. It is difficult however to guarantee that an LEE solution will not be destabilized at any point in the solution domain.…”
Section: Dealing With Kelvin-helmholtz (Kh) Instabilitiesmentioning
confidence: 99%